在线振动监测系统在减定径机组故障诊断中的应用分析 - 陈思龙; 黄颂光; 乔永钦 (Jixie Chuandong, 2013)
Because the reducing and sizing block shift gear bearings are installed in the gear,the operating conditions of bearing are unable to be directly detected.Through analyzing the spectrum of the reducing and sizing block B-box shift gear,combined with comparing the spectrum of before and after the fault,and the spectrum of the fault feature of shifting gears is analyzed in detail.Through the eccentric fault frequency of shift gears,the damage of the shift gear bearing is confirmed,it is better for the equipment maintenance persons to grasp and apply online vibration monitoring system to justify the level and the developing trend of the failure of bearings.Then,it is helpful for the equipment maintenance persons to predict the time of repair and tap the potential of equipments.